Clinical Features of Craniopharyngioma With Tumoral Hemorrhage: A Retrospective Case-Controlled Study - Chen, Yusi; Hu, Feng; Wang, Junwen; Huang, Kuan; Liu, Weihua; Tan, Yutang; Zhao, Kai; Xiao, Qungen; Lei, Ting; Shu, Kai (Frontiers in Surgery, 2022)
Background: Craniopharyngioma (CP) with tumoral hemorrhage is a very rare syndrome presenting with various manifestation and unfavorable outcomes. The current retrospective study was performed to summarize clinical features of CP with tumoral hemorrhage. Methods: 185 patients with pathological diagnosis of CP (18 hemorrhage patients) were enrolled. Clinical characteristics, radiological and surgical treatments, and postoperative complications were analyzed. Correlations between sexual hormones and tumor volume were also explored. Results: Drowsiness, acute syndrome, and pituitary deficiency were more frequent in hemorrhagic patients. Prothrombin time (PT) were higher in hemorrhagic patients. Luteinizing hormone (LH) and testosterone were lower in male patients with hemorrhage. Postoperative electrolyte disturbances, hypothalamic syndrome, and death appeared more frequently in the hemorrhage group. Moreover, prolactin (PRL) and cortisol 8AM were found to be correlated with the volume of the tumor and the hematoma respectively. Conclusion: The current study presented clinical features of CP apoplexy from aspects of clinical characteristics, radiography, surgical treatment and postoperative complications. Patients with CP apoplexy could benefit from proper processing of peritumoral hemorrhage and postoperative monitoring of the electrolyte.